Implementation of the Least Square Method in Tidal Harmonic Analysis Using Python Programming - rahmadania, Suci Fitra; Cahya, Ilham; Wicaksono, Ashari; Lailiyah, Inayatul (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
This study aims to analyze the tidal characteristics in the southern coastal area of ​​Madura using the least squares-based harmonic analysis method with Python programming. This method is used to obtain tidal harmonic constants and determine the tidal type in the study area. The analysis results show that the M₂ component is the dominant component with an amplitude of 0.498 m, followed by the K₁, O₁, and S₂. The Formzahl value of 1.056 indicates that the tidal type in the southern coastal area of ​​Madura is a mixed tide tending to be semidiurnal. Model validation using the Root Mean Square Error (RMSE) produced a value of 0.201 m, indicating that the modeling results have a fairly good level of accuracy. The results of this study are expected to be a reference in the planning and management of coastal areas in Madura waters.